Analisis Kinerja Keuangan Pada Anggaran Pendapatan Dan Belanja Daerah (APBD) Kabupaten Kebumen - Serli Marwati; Erny Pratiwi (Akuntansi research UGR, 2023)
Measuring financial performance is very important in assessing the accountability of local governments in managing local finances. The development of government financial performance can affect the community, because the greater the ability of a region to explore regional potential, not only to provide funds for the implementation of governance and regional development, but also to realize maximum services for the community. In analyzing the financial performance of local governments, it can be done by looking at the performance of the Budget Realization Report (LRA). This study aims to analyze the financial performance of the local government of Kebumen Regency in 2017-2021 based on the Ratio of Degrees of Fiscal Decentralization, Regional Financial Dependence, Regional Financial Independence, Effectiveness of Regional Original Revenue and Efficiency of Regional Original Income. The analysis technique used is quantitative descriptive. The data used is secondary data in the form of Kebumen Regency APBD and LRA reports for 2017 – 2021 obtained from the official website of www.djpk.kemenkeu.go.id. The results of this study show the financial performance of the local government of Kebumen Regency in 2017 – 2021 based on the Fiscal Decentralization Degree Ratio with an average of 15.09%, based on the Regional Financial Dependence Ratio with an average of 23.49%, based on the Regional Financial Independence ratio with an average of 64.59%, based on the average Regional Original Revenue Effectiveness ratio of 117%, and based on the Regional Original Revenue Efficiency ratio with an average of 98.87%.